A series of tunable emission phosphors of Sm3+, Eu3+ and Mn2+ doped Ba3Tb(PO4)3: luminescence and energy transfer1. Issue 88 (25th September 2015) - Li, Ting; Li, Panlai; Wang, Zhijun; Xu, Shuchao; Bai, Qiongyu; Yang, Zhiping
<x xml:space="preserve">Abstract</x> A series of activator Sm3+, Eu3+, Mn2+ ion doped Ba3Tb(PO4)3 phosphors with tunable emitting color were synthesized via the high temperature solid state method.